Policy effectiveness and capacity: two sides of the design coin - MUKHERJEE, Ishani (Institutional Knowledge at Singapore Management University, 2019)
Policy capacity and effectiveness are two themes that have opened new pathways for academic and empirical enquiry throughout the policy sciences. In the contemporary discourse of policy design, effectiveness has taken on a more foundational meaning that goes beyond what is understood as only the attainment of specific policy goals. Rather, it has come to occupy a central position in the study of policy design, signifying the broader logic of deliberate policy action used to articulate policy problems and present alternative ways of addressing them. Effectiveness thus signals both effectual processes as well as successful policy outcomes. However, what constitutes effective design is a question that still reflects a largely dispersed body of research within the policy sciences. This article and others in this special issue, aim to address the topic of effective design from the perspective of capacity, defined as the inherent analytical, managerial and political capabilities of policymakers to bring about effective policy solutions.